2020
DOI: 10.5009/gnl19171
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound-Guided Tissue Acquisition by 22-Gauge Franseen and Standard Needles for Solid Pancreatic Lesions

Abstract: Background/Aims: Recently, a three-plane symmetric needle with Franseen geometry was developed for endoscopic ultrasound-guided fine needle biopsy (EUS-FNB). In this retrospective study, tissue acquisition per pass was compared between 22-gauge Franseen FNB and standard fine needle aspiration (FNA) needles in patients with solid pancreatic lesions. Methods: Consecutive patients who underwent EUS-FNA or EUS-FNB for solid pancreatic lesions between October 2014 and March 2018 were retrospectively studied. The ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…As for procedure-related adverse events, EUS-FNB was associated with a higher adverse event rate than EUS-FNA in our study, though this was not statistically significantly (20.0% vs. 0%, p = 0.143). Previous studies comparing EUS-FNA and EUS-FNB for solid pancreatic mass reported no significant difference in adverse event rates [ 16 , 19 , 44 ]. Since the adverse event rate of EUS-FNB in our cohort appeared too high, further investigation with a larger cohort is warranted.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As for procedure-related adverse events, EUS-FNB was associated with a higher adverse event rate than EUS-FNA in our study, though this was not statistically significantly (20.0% vs. 0%, p = 0.143). Previous studies comparing EUS-FNA and EUS-FNB for solid pancreatic mass reported no significant difference in adverse event rates [ 16 , 19 , 44 ]. Since the adverse event rate of EUS-FNB in our cohort appeared too high, further investigation with a larger cohort is warranted.…”
Section: Discussionmentioning
confidence: 97%
“…Fifty percent of patients were diagnosed with pathologically definite LPSP in patients who underwent EUS-FNB, though none were diagnosed of those who underwent EUS-FNA (50.0% vs. 0%, p = 0.002). FNB needles can acquire a larger amount of tissue with better preservation of tissue architecture than FNA needles [ 17 , 19 , 41 , 42 ]. Thus, special staining, such as Elastica van Gieson staining and IgG4 immunostaining, can be performed and is speculated to improve diagnostic yield of EUS-FNB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, the ultrasound-guided biopsy exerted an important role in pre-operative diagnosis. Nowadays, the value of endoscopic ultrasonography for the differential diagnosis of various pancreatic lesions (malignant, low-grade malignant, and benign) has been widely depicted[ 18 - 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the available literature, FNB has shown a diagnostic yield of more than 90 % [14]. Moreover, the diagnostic performance of FNB sampling of pancreatic masses was significantly better than FNA sampling, and was also associated with ease of diagnosis and shorter viewing times by the pathologists [15].…”
Section: Is Fnb Better Than Fna?mentioning
confidence: 99%